Development of a needs-based career awareness program for the Letran-Calamba intermediate grade school pupils - Gonzales, Marianne G. (Animo Repository, 2008)
The primary objective of this research was to develop a Needs-Based Career Awareness Program for Letran Intermediate Grade School Pupils. This descriptive research had one hundred eighty (180) intermediate pupils, one hundred seventeen (117) parents, nine (9) class advisers, four (4) guidance counselors, one (1) principal and one (1) Student Development Director who served as respondents and participants in the administration of the three researcher-made instruments namely the Children’s Need Checklist, the Program Evaluation by the Advisers, Guidance Counselors and Department Heads and the Program Evaluation by the Pupils. The results of the assessment were analyzed using frequency, percentage and mean analysis. On the perceived needs of the pupils, this research found that pupils were concerned primarily with knowing themselves, discovering what they could do, becoming responsible for their actions and having willingness to accept corrections. They valued having an attractive appearance and good health. They wanted to be loved, understood and respected as a person. They also valued a happy and peaceful home life. They would like to be considered and be accepted as good friends especially by their peer group. As for school concerns, they would like to improve their academic performance and to have the needed academic skills like improving their study habit or attitude toward study and managing their time. Their major career concerns were to know the characteristics to be considered in choosing a future career, to know what they really want to become and to be guided in their career planning and decision-making process. With the above needs assessment result, the researcher designed a Needs-Based Career Awareness Program consisting of its purposes, contents, management/operational plan, and evaluation plan. The advisers, guidance counselors and department heads identified the program purposes, program content, and evaluation as the strengths of the proposed program. On the other hand, the area that needed improvement was the management/operational plan component. The program evaluation, as assessed by the pupils, revealed a very satisfactory rating based on the overall satisfaction with the program. The researcher thus recommended the educators to consider needs-based educational programs to improve their accountability and the learning of the pupils. Followup researches on the creation of modules of activities, evaluation system, as well as evaluation tool were also recommended.